Necesidad de reformar el capitulo v de la ley orgánica de garantías jurisdiccionales y control constitucional con respecto al procedimiento a seguirse para la Interposición de la acción de acceso a la Información publica. - Buenaño Guerrero, Luis Alberto (2012)
The overall purpose of this preliminary investigation to obtain the title of Bachelor of Jurisprudence, is to establish the NEED FOR REFORM CHAPTER V OF THE ORGANIC LAW COURTS AND CONTROL OF CONSTITUTIONAL GUARANTEES WITH RESPECT TO THE PROCEDURE TO BE FOLLOWED FOR THE FILING OF ACTION FOR ACCESS A PUBLIC INFORMATION. This research is intended mainly to make a general study of constitutional safeguards adopted by the new Constitution of our country, and, with this study approach the so-called Action for Access to Public Information, which will analyze in order to understand full extent of the law. With the approval of the new constitution, we proceeded to make a major reform in relation to the institution of constitutional guarantees to that effect was included as a constitutional Resource Access to Public Information. In forming the Action on Access to Public Information in a constitutional, it is necessary for your procedure suits the new rules introduced in the latest amendments to the Constitution and the Organic Law of Guarantees Jurisdictional and Constitutional Control, making it have to be made a specific procedure to date and legally appropriate to the new constitutional arrangements, so that the process itself to initiate this action, recorded in the Law of Guarantees Jurisdictional and Constitutional Control, this in view that the regulations apply previously mentioned reforms has become irrelevant. In this regard, due to the existence of regulatory diversity in our country on the right of access to public information, it is necessary to clearance through appropriate legal procedures are harmonized into a single body of law that allows an effective exercise of that right, and proper and expeditious protection of the laws in force on the right of access to public information.